WearWrite: Orchestrating the Crowd to Complete Complex Tasks from Wearables - Nebeling, Michael; Guo, Anhong; To, Alexandra; Dow, Steven; Teevan, Jaime; Bigham, Jeffrey (Proceedings of the 28th ACM User Interface Software and Technology Symposium (UIST 2015), Charlotte, NC, 2015)
Smartwatches are becoming increasingly powerful, but limited input makes completing complex tasks impractical. Our WearWrite system introduces a new paradigm for enabling a watch user to contribute to complex tasks, not through new hardware or input methods, but by directing a crowd to work on their behalf from their wearable device. WearWrite lets authors give writing instructions and provide bits of expertise and big picture directions from their smartwatch, while crowd workers actually write the document on more powerful devices. We used this approach to write three academic papers, and found it was effective at producing reasonable drafts.